Performance of uplink WFRFT‐based hybrid carrier systems with non‐orthogonal multiple access. Issue 15 (23rd August 2018) - Wang, Xiaolu; Labeau, Fabrice; Mei, Lin; Wang, Zhenduo; Sha, Xuejun
Abstract : In this paper, the performance of hybrid carrier (HC) systems based on weighted fractional Fourier transform (WFRFT) is investigated in an uplink non‐orthogonal multiple access (NOMA) scenario. NOMA is a promising technology to improve the system capacity, in which two users (far‐user and near‐user relative to a base station) are allocated to use the same time‐frequency resources, and the successive interference cancellation (SIC) technique is implemented to decode signals at the receiver. Considering the actual error decoding in the SIC process (i.e. imperfect SIC), NOMA cannot avoid the inter‐user interference (IUI) and residual interference (or error propagation). Therefore, firstly IUI and residual interference are analysed, and signal to interference plus noise ratio (SINR) of the far‐user is expressed mathematically considering the residual interference. Then, based on the analysis of IUI, considering different WFRFT orders, a near‐user BER expression over additive white Gaussian noise (AWGN) channels is derived. Furthermore, the optimal WFRFT order selection to minimise the interference influence in the uplink is formulated and solved efficiently. Simulation results have verified the mathematical expression of SINR, the near‐user theoretical BER expression, and the proposed optimal WFRFT order selection to obtain the maximum sum spectral efficiency.